Multifunctional Semi-interpenetrating Superabsorbents from Graft Polymerization of Acrylic Acid on Cellulose in Presence of Fulvic Acid as Potential Slow Release Devices of Soil Nutrients - Essawy, Hisham (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
<span style="line-height: 115%; font-family: ’Arial’,’sans-serif’; font-size: 9pt; mso-fareast-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Grafting polymerization of acrylic acid (AA) was undertaken onto cellulose powder (Cell) in presence of potassium fulvate (KF) to produce semi-interpenetrating network structures. The grafting efficiency (GE) and grafting yield (GY) were studied as and indicated that the grafting process was not influenced in presence of KF. KF was expected to be incorporated into the cellulose backbone in the same course of the graft polymerization via polycondensation with groups from cellulose and monomer. The simultaneous graft polymerization of acrylic acid and polycondensation processes of all components allows formation of a more chemically active semi-interpenetrating network structure. Successful incorporation of KF to the network structure was predicted from fourier transform infrared spectroscopy (FTIR) while enhanced Cu2+ uptake confirmed the better chemical activity with respect to the same network prepared in absence of KF. Furthermore, the wide variation of the swelling potential as a function of the pH further corroborates the insertion of KF to the network structure. Imaging with scanning electron microscopy (SEM) indicated morphological alteration on the surface which might be related to the KF anchoring to the cellulose backbone. The developed superabsorbents showed increment in the water absorption both in distilled water and salted solutions as well. The newly developed superabsorbent was applied as a support for soil nutrients and their controlled release in soil was studied. The results proved efficiency of the superabsorbent to warrant appropriate release of the nutrients according to the time regulations set by European Committee of Normalization (ECN). Improved water retention was also an additional advantage.